2018
DOI: 10.1111/1365-2745.13102
|View full text |Cite
|
Sign up to set email alerts
|

Plant functional groups mediate drought resistance and recovery in a multisite grassland experiment

Abstract: Climate change predictions suggest that summer droughts will become more intense and recurrent in Europe. While drought‐induced reductions in grassland primary productivity are well documented, the drivers behind drought resistance (the capacity to withstand change) and recovery (the capacity for recovery of function) of above‐ and below‐ground biomass remain poorly understood. Across eight grasslands differing in plant community productivity (CP), we investigated the effects of summer drought on plant and soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 66 publications
7
87
0
Order By: Relevance
“…Ecosystems dominated by exploitative plant species produce more biomass of greater nutritional quality (Gardarin et al, ; Lavorel et al, ), with faster litter decomposition (Fortunel et al, ; Quested, Eriksson, Fortunel, & Garnier, ) and faster mineralization and nitrification (Grigulis et al, ; Orwin et al, ), as compared with ecosystems dominated by conservative plants. Exploitative plant species are also less resistant to drought, but with faster recovery (Karlowsky et al, ; Mackie, Zeiter, Bloor, & Stampfli, ). This continuum from slow to fast nutrient cycling along the plant economics spectrum has also been related to concomitant changes in soil microbial community composition and resilience: bacteria dominate at the exploitative end of the continuum and fungi at the conservative one, with respectively greater resilience and stronger resistance to drought (Cole et al, ; De Vries, Liiri, et al, ; De Vries, Manning, et al, ; De Vries & Shade, ; Grigulis et al, ; Legay et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ecosystems dominated by exploitative plant species produce more biomass of greater nutritional quality (Gardarin et al, ; Lavorel et al, ), with faster litter decomposition (Fortunel et al, ; Quested, Eriksson, Fortunel, & Garnier, ) and faster mineralization and nitrification (Grigulis et al, ; Orwin et al, ), as compared with ecosystems dominated by conservative plants. Exploitative plant species are also less resistant to drought, but with faster recovery (Karlowsky et al, ; Mackie, Zeiter, Bloor, & Stampfli, ). This continuum from slow to fast nutrient cycling along the plant economics spectrum has also been related to concomitant changes in soil microbial community composition and resilience: bacteria dominate at the exploitative end of the continuum and fungi at the conservative one, with respectively greater resilience and stronger resistance to drought (Cole et al, ; De Vries, Liiri, et al, ; De Vries, Manning, et al, ; De Vries & Shade, ; Grigulis et al, ; Legay et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Bloor and Bardgett (2012) and also Denton et al (2017) found that drought events promote soil fertility and nutrient retention following drought release. Likewise, Gordon et al (2008) found an increase in microbial activity after a rewetting event, possibly leading to a rapid and sudden influx of plant available nitrogen in the soil (Mackie et al, 2018;Schimel and Bennett, 2004). Hofer et al (2017a) also attributed growth increases relative to control plots in post-drought periods to nitrogen availability in the soil and Karlowsky et al (2018) found evidence that interactions between plants and microbes increase plant nitrogen uptake in grasslands after rewetting events.…”
Section: Positive Legacy Effects Of Drought Periodsmentioning
confidence: 94%
“…Effects of drought on annual aboveground NPP of grasslands have been shown to vary, depending on the severity of the experienced drought (Vicca et al, 2012;Wilcox et al, 2017), ecosystem type (Byrne et al, 2013;Gherardi and Sala, 2019;Sala et al, 2015;Wilcox et al, 2017), the intensity of land use (Vogel et al, 2012;Walter et al, 2012), the plant functional composition (Gherardi and Sala, 2015;Hofer et al, 2016Hofer et al, , 2017aMackie et al, 2018), or the biodiversity of an ecosystem (Isbell et al, 2015;Kahmen et al, 2005;Wagg et al, 2017). In accordance with work in C4 grasslands, our study shows that the timing of a drought event in the growing season is crucial for the immediate effects of a drought https://doi.org/10.5194/bg-2020-100 Preprint.…”
Section: Small To Moderate Impact Of Seasonal Drought On Annual Abovementioning
confidence: 99%
See 2 more Smart Citations